E-LEARNING PLATFORM FOR START-UP SIMULATION IN LIFE SCIENCE AND BUSINESS FIELD – A USEFUL EDUCATIONAL TOOL - Radu Cristian TOMA; Gabriela MARGARIT; Gabriel GARAIS; Florentina MATEI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
During an Erasmus+ KA2 project implementation, an international team has developed an e-learning platform useful as an educational tool for Start-up simulation in the field of Life Sciences A video tutorial is also available for the use of the platform; the tutorial is embedded from YouTube. The Database structure has two main data types called: Simulation Business Game and Company for The Business Model Canvas. Each of the “Simulation Business Game” has many potential “Companies for The Business Model Canvas”. The platform offers centralized knowledge management in innovation and entrepreneurship containing reference documents that can be used in specific activities related to simulated enterprise and start-ups, giving also access to located resources according to the national character and specific legislation for each of the users.